(untitled) - Dean, Tamara (Austrlia, 2006)
This book is intended to serve the needs of students and professionals who are interested in mastering fundamental, vendor-independent networking concepts. Network+ Guide to Networks offers some important guidance to those seeking to enhance their general knowledge about transmission media, network protocols, topology methods, remote connectivity, wireless and network operating systems.
Keywords: Telecommunications engineers,Telecommunications engineers; Certification,Study guides,Certification,Study guides